Transformasi Perilaku Sosial Remaja di Era Digital: Penggunan Tiktok di Kalangan Remaja Beji Boyolali - Kusuma, Caesar Davala; Prajoko, Roso; Chumaeson, Wahyuning (Prodi Ilmu Komunikasi Universitas Sahid Surakarta, 2024)
In the rapid development of the digital era, technology is an important part of teenagers' lives. One of the results of the development of the digital era is social media, Tiktok. Teenagers' tendency to Tiktok can have various impacts felt by teenagers. This study aimed to determine the impact of using Tiktok for teenagers and how Tiktok could change the social behavior of teenagers in Dukuh Beji, Sidomulyo Village, Ampel District, Boyolali Regency, using the theory of social change, and uses and effect. The type of research was descriptive qualitative with data collection techniques: observation, interviews, documentation study. The results of the study that (1) Teenagers got addiction and tendency to the Tiktok application. Teenagers used Tiktok to find information, but mostly used it to find entertainment. (2) Tiktok had a significant impact on teenagers. There were negative and positive impacts felt by teenagers. (3) Teenagers experience changed in social behavior due to the use of Tiktok such as lazy behavior, lifestyle changes, decreased ethics and manners when speaking, and lack of social participation. The implication of this research is to provide an explanation of the transformation of adolescent social behavior by using social media, especially Tiktok.